Math, asked by gurudevrajak786, 6 months ago

4a²-9b²-2a-3b? factories ​

Answers

Answered by muhamadsameer226
1

4a² - 9b² - 2a - 3b

.

write the first two terms in perfect square:

= (2a)² - (3b)² - (2a + 3b)

.

Apply (a² - b²) = (a + b)(a - b):

= (2a + 3b) (2a - 3b) - (2a + 3b)

.

Take out common factor (2a + 3b):

= (2a + 3b) [ (2a - 3b) - 1 ]

.

Evaluate the second bracket:

= (2a + 3b)( 2a - 3b - 1)

.

Answer: (2a + 3b)( 2a - 3b - 1)


muhamadsameer226: GAVE ME THE BRAINLIEST IF MY ANSWER WAS HELPFUL
Answered by Anonymous
0

 \sf \:  {4a}^{2}  -  {9b}^{2}  - 2a - 3b \\  \sf \implies \:  {(2a)}^{2}  -  {(3b)}^{2}  - (2a + 3b) \\  \sf \implies \: (2a + 3b)(2a - 3b) \: -  \:  (2a + 3b) \\  \sf \implies \: (2a + 3b) \: ((2a - 3b) - 1) \\  \red{ \sf \implies \: (2a + 3b) \: (2a - 3b - 1)}

Similar questions